Social reappraisal of emotions is linked with the social presence effect in the default mode network - Xie, Xiyao; Bertram, Teresa; Zorjan, Saša; Horvat, Marina; Sorg, Christian; Mulej Bratec, Satja (Frontiers in Psychiatry, 2023)
Social reappraisal, during which one person deliberately tries to regulate another’s emotions, is a powerful cognitive form of social emotion regulation, crucial for both daily life and psychotherapy. The neural underpinnings of social reappraisal include activity in the default mode network (DMN), but it is unclear how social processes influence the DMN and thereby social reappraisal functioning. We tested whether the mere presence of a supportive social regulator had an effect on the DMN during rest, and whether this effect in the DMN was linked with social reappraisal-related neural activations and effectiveness during negative emotions. A two-part fMRI experiment was performed, with a psychotherapist as the social regulator, involving two resting state (social, non-social) and two task-related (social reappraisal, social no-reappraisal) conditions. The psychotherapist’s presence enhanced intrinsic functional connectivity of the dorsal anterior cingulate (dACC) within the anterior medial DMN, with the effect positively related to participants’ trust in psychotherapists. Secondly, the social presence-induced change in the dACC was related with a) the social reappraisal-related activation in the bilateral dorsomedial/dorsolateral prefrontal cortex and the right temporoparietal junction and b) social reappraisal success, with the latter relationship moderated by trust in psychotherapists. Results demonstrate that a psychotherapist’s supportive presence can change anterior medial DMN’s intrinsic connectivity even in the absence of stimuli and that this DMN change during rest is linked with social reappraisal functioning during negative emotions. Data suggest that trust-dependent social presence effects on DMN states are relevant for social reappraisal – an idea important for daily-life and psychotherapy-related emotion regulation.